2022
DOI: 10.3389/fimmu.2022.979995
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related SERPINA3 as a biomarker involved in diabetic nephropathy renal tubular injury

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease and has become a serious medical issue globally. Although it is known to be associated with glomerular injury, tubular injury has been found to participate in DN in recent years. However, mechanisms of diabetic renal tubular injury remain unclear. Here, we investigated the differentially expressed genes in the renal tubules of patients with DN by analyzing three RNA-seq datasets downloaded from the Gene Expression Omnibus database. Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Studies have suggested that Spi2a contributes to memory T cell development, controls the viability of Th2 cells, and mediates B-cell and granulocyte formation 34 37 . SERPINA3 , the human orthologue of Spi 2a , is also identified to be an inflammation-related gene and closely associated with immune responses 38 , 39 . However, the function of Spi2a in macrophages in the context of sepsis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that Spi2a contributes to memory T cell development, controls the viability of Th2 cells, and mediates B-cell and granulocyte formation 34 37 . SERPINA3 , the human orthologue of Spi 2a , is also identified to be an inflammation-related gene and closely associated with immune responses 38 , 39 . However, the function of Spi2a in macrophages in the context of sepsis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Serine protease inhibitor A family member 3 (SERPINA3) acts primarily as a protease inhibitor and plays an important role in the regulation of cellular processes such as oxidative stress, fibrosis, angiogenesis, inflammatory response and apoptosis ( 46 , 47 ) In diabetic nephropathy, immune-related SERPINA3 inhibits mast cell proliferation and activation by downregulating chymase activity, thereby alleviating disease progression ( 48 ). During tumor progression, STAT3-dependent SERPINA3 enhances tumor cell invasion, migration, and angiogenesis ( 46 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…ClusterProfile in R was used for GO analysis, and only items with p < 0.05 were considered significantly enriched. (Fan et al 2022)…”
Section: Methodsmentioning
confidence: 99%